Development Of Inorganic Membrane To Remove Oil Emulsifier From Domestic Waste water. - Najafpour, Ghasem; Ahmad, Latif (Universiti Sains Malaysia, 2003)

(untitled)
The rapid development of membranes in waste water treatment was a great encouragement to participate and fabricate inorganic membrane. The results yielded to an expansion of knowledge and producing various types of ceramic membrane. The ceramic membrane has a great potential and market, ceramic membrane represents a distinct class of inorganic membranes, especially the metallic coated has many industrial application. The porous ceramic was prepared for to fabricate the supported membrane. A thin film of Aluminium and Zirconium were formed. Unsupported membrane was also prepared.